Проблеми урбанізації - Омельченко, М. Д. (ХНУРЕ, 2021)
A Society has crossed the significant border recently : an urban population has jumped over the country one. There are a lot of reasons for that statement, and it has changed our lifestyle significantly. The urbanisation is an awesome subject of disputes nowadays, the particular reason for this circumstance is it’s novelty, and the overwhelming majority of publicity literally can’t understand all factors that have an impact on human living ability in urbanistic areas.
Keywords: проблеми урбанізації; урбанізація